2006
DOI: 10.1149/1.2209384
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Tungsten Carbides as Alkaline Fuel Cell Catalysts

Abstract: The applications of transition metal carbides as catalysts had received a great deal of interest since the discovery of their catalytic activities. In the present study, nano W2C powders with high surface area were synthesized by the microwave irradiation method. X-ray diffraction measurement confirmed the product is crystalline tungsten carbide, which could be pure W2C or the mixture of W2C and WC. TEM results showed that tungsten carbide powders are uniformly dispersed with the particle size around 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…2 It was also reported that the addition of WC to Pt, Pd, Au and other precious or base metals can enhance the activity toward the oxygen reduction reaction (ORR) in both acidic and alkaline solutions. [3][4][5][6][7][8][9] The improved catalytic activity is believed to be due to the synergistic effect between metal nanoparticles and WC. [10][11][12] In additions to tungsten carbide, molybdenum carbide was also reported as an effective electrocatalyst support.…”
Section: Introductionmentioning
confidence: 99%
“…2 It was also reported that the addition of WC to Pt, Pd, Au and other precious or base metals can enhance the activity toward the oxygen reduction reaction (ORR) in both acidic and alkaline solutions. [3][4][5][6][7][8][9] The improved catalytic activity is believed to be due to the synergistic effect between metal nanoparticles and WC. [10][11][12] In additions to tungsten carbide, molybdenum carbide was also reported as an effective electrocatalyst support.…”
Section: Introductionmentioning
confidence: 99%
“…52 Contrary to expectations, however, the intrinsic ORR activity of WC directly applied in alkaline media is extremely low. 53 Emerging materials and composites have shown great promise for ORR catalysis. Among these materials, MXenes have proven to be conducting fortifiers to composites as they demonstrate strong interfacial coupling interaction and fast charge transfer.…”
Section: Orr In Alkaline Electrolytesmentioning
confidence: 99%
“…The mixture of W 2 C and WC has good methanol tolerance as its activity was not affected by the presence of methanol. 78 A series of interstitial metal carbides (M ¼ Zr, Ti, V, Mo, W, Nb, Ta) investigated by Horigome et al were incorporated in Raney Ni and PTFE based gas diffusion electrodes for hydrogen oxidation. ZrC provided highest performance with respect to the electrode stability and polarization characteristics.…”
Section: Non-pt Based Catalystsmentioning
confidence: 99%